2007
DOI: 10.1088/0957-4484/18/42/424027
|View full text |Cite
|
Sign up to set email alerts
|

Blinking suppression and intensity recurrences in single CdSe-oligo(phenylene vinylene) nanostructures: experiment and kinetic model

Abstract: We report time-resolved single molecule fluorescence imaging of individual CdSe quantum dots that are functionalized with oligomeric conjugated organic ligands. The fluorescence intensity trajectories from these composite nanostructures display both a strong degree of blinking suppression and intensity fluctuations with characteristic recurrence times on the order of 10-60 s. In addition, fluorescence decay rate measurements of individual hybrid nanostructures indicate significantly modified non-radiative quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 31 publications
3
42
1
Order By: Relevance
“…In terms of statistics, these time constants imply that 5,208 and 384 photons can be counted for a unit second as the fluorescence intensities of "on" and "off" states. Figure 4(b) strongly demonstrates that emissions of single NCs flow between two levels ("on" and "off" states) contrary to the previous reports of continuous distribution in emission intensity [18,19].…”
Section: Time Constants and Thresholdcontrasting
confidence: 68%
See 1 more Smart Citation
“…In terms of statistics, these time constants imply that 5,208 and 384 photons can be counted for a unit second as the fluorescence intensities of "on" and "off" states. Figure 4(b) strongly demonstrates that emissions of single NCs flow between two levels ("on" and "off" states) contrary to the previous reports of continuous distribution in emission intensity [18,19].…”
Section: Time Constants and Thresholdcontrasting
confidence: 68%
“…Verberk et al suggested a charged "on" state in terms of trap depth [12]. Extending the prolonged "on" state to a three-state model, recent reports [18,19] have suggested that emission states of single NCs are governed by not two levels ("on" and "off") but numerous intermediate levels of continuous distribution. However, we noted that the temporal resolutions of these previous studies were limited to 10-100 ms/bin.…”
Section: Introductionmentioning
confidence: 99%
“…Since last two decades, semiconductor nanoparticles have attracted considerable attention because of their size dependent electronic properties arising from the quantum confinement of electron [1][2][3][4][5][6][7]. II-VI semiconductor materials are recently more important for the optoelectronic devices as well as solar cells fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…[32] This pioneering work concerning the passivation of electron surface traps by electron-donating groups was extended to conjugated organic ligands oligo(phenylenevinylene). [33] In this work, lifetime time-resolved measurements showed that the blinking reduction comes from a reduction of the lifetime of the electron-hole pair. Since the carriers of the excited electron hole pair have less time to cross the shell of the nanocrystal, blinking is reduced.…”
mentioning
confidence: 72%